Macroporous beads for lipase immobilization: kinetic resolution of a racemic drug intermediate - Bhushan, Indu; Parshad, Rajinder; Qazi, G. N.; Ingavle, Ganesh C.; Jamalpure, Trupti M.; Rajan, C. R.; Ponrathnam, Surendra; Gupta, V. K. (Journal of Bioactive and Compatible Polymers, 2007)
{Lipase isolated from Arthrobacter sp. (RRLJ-1, MTCC No. 5125, named ABL), is effective in resolving a wide range of racemic drug intermediates. In this study, ABL was immobilized on a series of synthetic macroporous epoxy copolymers beads with varying pore sizes, surface area and hydrophobicity. Poly(glycidyl methacrylate-co-ethylene dimethacrylate) beads, with 75% crosslink density and 10% of epoxy groups modified with dibutyl amine [
Keywords: auxin pulse; coco-peat; grape; micropropagation; plantlet survival

Lipase enzyme immobilization on synthetic beaded macroporous copolymers for kinetic resolution of chiral drugs intermediates - Bhushan, Indu; Parshad, Rajinder; Qazi, Gulam Nabi; Ingavle, Ganesh C.; Rajan, C. R.; Ponrathnam, Surendera; Gupta, Vijay Kumar (Process Biochemistry, 2008)
Lipase isolated from Arthrobacter sp. (bacterial strain, MTCC No. 5125) at RRL Jammu, being used for various process development. Arthrobacter sp. lipase (ABL) now has been immobilized on synthetic polymers and reused many a times. In this investigation number of various synthetic macroporous alkylated glycidyl epoxy copolymers with varying hydrophobicity, pore volume and surface area were prepared and used for this study. Among all the polymers prepared and used only two epoxy polymers GMA-EGDM 75-20(I) and GMA-EGDM 75-30(I) with particle size in the range of 150-450 nm, epoxy groups 80 and 70%, tertiary amino groups 20 and 30% was found suitable for immobilization of lipase (ABL). Dibutyl amine (DBA) incorporation created an internal pore radii 20-50 nm and hydrophobic microenvironment in both the polymers for binding the enzyme, which led to improvement in stability and enatioselectivity in racemic resolution process especially by binding to one of the isomers. The optimal ABL binding capacity of polymer GMA-EGDM 75-20(I) was 60 units, 34 mg protein and GMA-EGDM 75-30(l) was 36 units, 21 mg protein/g polymer. The immobilized lipase matrices displayed enhanced pH, thermal, organic solvent and long-term storage stability. Both the immobilized enzyme matrices were tested firstly for the hydrolysis of triglycerides using tributyrin as substrate. After testing, both the matrices were reused for racemic resolution of ethyl-3-hydroxy-3-phenyl propanoate (fluoxetine intermediate, an antidepressant drug) and racemic chiral auxiliary, acetyl-1-phenyl ethanol (intermediate of many chiral drugs) for 15 cycles. These immobilized lipase matrices have shown very high stability on recycling, high-enantioselectivity, high conversion and faster recovery of product compare to free enzyme, therefore these matrices may find use in kinetic resolution process developments. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: 1-phenyl ethanol and enantioselectivity; chiral resolution; enantiomeric excess (ee); ethyl-3-hydroxy-3-phenyl propanoate; Immobilization; Lipase

Arthrobacter sp lipase immobilization for preparation of enantiopure masked beta-amino alcohols - Chaubey, Asha; Parshad, Rajinder; Gupta, Pankaj; Taneja, Subhash C.; Qazi, Ghulam N.; Rajan, C. R.; Ponrathnam, S. (Bioorganic & Medicinal Chemistry, 2009)
Recent reports on immobilization of lipase from Arthrobacter sp. (ABL, MTCC 5125; IIIM isolate) on insoluble polymers have shown altered properties including stability and enantioselectivity. Present work demonstrates a facile method for the preparation of enantiopure beta-amino alcohols by modulation of ABL enzyme properties via immobilization on insoluble as well as soluble supports using entrapment/covalent binding techniques. Efficacies of immobilized ABL on insoluble supports prepared from tetraethylorthosilicate/aminopropyltriethoxy silane and soluble supports derived from copolymerization of N-vinyl pyrrolidone-allylglycidyl ether (ANP type)/N-vinyl pyrrolidone-glycidyl methacrylate ( GNP type) for kinetic resolution of masked beta-amino alcohols have been studied vis-a-vis free ABL enzyme/wet cell biomass. The immobilized lipase on different insoluble/soluble supports has shown 21 - 110 mg/g protein binding and 30 - 700 U/g activity for hydrolyzing tributyrin substrate. The findings have shown a significant enhancement in enantioselectivity (ee 99%) vis-a-vis wet cell biomass providing ee 70-90% for resolution of beta-amino alcohols. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Arthrobacter sp lipase; beta-Aminoalcohol; Enantioselectivity; Immobilization; soluble polymer

Immobilization of enantioselective lipase on soluble supports for kinetic resolution of drug intermediates - Chaubey, Asha; Parshad, Rajinder; Taneja, Subhash C.; Deokar, Sarika Babasaheb; Raman, Rajan C.; Ponrathnam, Surendra (Journal of Bioactive and Compatible Polymers, 2012)
The microbial lipase, Arthrobacter sp. lipase (MTCC 5125), from the Indian Institute of Integrative Medicine repository, is known as an effective catalyst for high enantioselective kinetic resolution of drug intermediates. The ABL was immobilized on water-soluble linear supports by covalently binding it to the epoxy groups on the N-vinyl pyrrolidone/allyl glycidyl ether and N-vinyl pyrrolidone/glycidyl methacrylate copolymers. The immobilized lipase, on different soluble supports, had 90-110 mg/g protein binding and 500-700 U/g hydrolysis activities for tributyrin substrate. These copolymers had soluble/insoluble characteristics in different pH ranges, which is an advantage over insoluble copolymers. A soluble polymer at neutral pH provided better accessibility to the immobilized enzyme, which was recovered by precipitation at pH 2-3 for reuse. Kinetic resolution of racemic acyl derivatives of chiral auxiliaries and drug intermediates, namely, phenyl ethanol, aminoalcohol, and fluoxetine intermediate resulted in a significant enhancement in enantioselectivity (99%).
Keywords: Arthrobacter sp lipase; Enantioselectivity; Immobilization; Kinetic resolution; N-vinylpyrrolidone; soluble polymer